Passively Q-Switched Er-Doped Fiber Laser Based on Bentonite Clay (Al2H2O6Si) Saturable Absorber - Haroon Asghar; Umer Sayyab Khalid; Muhammad Sohail; Tahani A. Alrebdi; Zeshan A. Umar; A. M. Alshehri; Rizwan Ahmed; M. Aslam Baig (Micromachines, 2024)
This paper presents the investigations toward the direct use of bentonite clay (Al2H2O6Si) nanoparticles to act like a saturable absorber (SA) for the Q-switched pulse operation of an erbium-doped fiber laser (EDFL). The measured results reveal that with the incorporation of bentonite clay nanopowder as a SA, an EDFL is realized with a Q-switching mechanism starting at a pump power of 30.8 mW, and a Q-switched emission wavelength was noticed at 1562.94 nm at 142 mW pump power. With an increased pump from 30.8 mW to 278.96 mW, the temporal pulse parameters including minimum pulse duration and maximum pulse repetition rates were reported as 2.6 µs and 103.6 kHz, respectively. The highest peak power, signal-to-noise ratio, output power and pulse energy were noticed to be 16.56 mW, 51 dB, 4.6 mW, and 47 nJ, respectively, at a highest pump power of 278.96 mW. This study highlights the significance of bentonite clay (Al2H2O6Si) nanoparticles as a potential candidate for a saturable absorber for achieving nonlinear photonics applications.